ONLINE AND E-LEARNING EDUCATION AND ITS ROLE IN MODERN EDUCATION - Axmedova Sevara; Adilova Muslima (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Similarly, varieties of terms connected to online and distance learning have also evolved in the wake of them becoming more established learning pathways. Online and distance learning platforms have evolved to include features such as Learning Management Systems (LMSs), Application Programming Interface (APIs), and Massive Open Online Course (OLX) among others. Such terms signify different features attributed to online and distance learning methods and tools. As such, deciding on a course becomes easier once you understand what each type of learning offers. So let’s take a look at eLearning vs online learning.